2010
DOI: 10.1007/s00044-010-9329-y
|View full text |Cite
|
Sign up to set email alerts
|

Design, docking study and ADME prediction of Isatin derivatives as anti-HIV agents

Abstract: Non-nucleoside reverse transcriptase inhibitors (NNRTI) has a definitive role and most commonly used in treatment of HIV infection. NNRTI act by binding to specific binding site (non-nucleoside binding pocket-NNBP) in reverse transcriptase (RT) enzyme. With the objective of developing efficient NNRTI, we have designed various Isatin analogs for effective treatment of AIDS and were subjected to molecular docking studies on five different crystal structures of RT complexed with five different ligands Nevirapine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Isatin derivatives revealed a fascinating array of pharmacological activities, such as anticancer [ 10 ], anti-HIV [ 11 ], antiviral [ 12 ], antitumor [ 13 ], antifungal [ 14 ], antimalarial [ 15 ], antioxidant [ 16 ], anti-inflammatory [ 17 ], antimicrobial [ 18 ], analgesic [ 19 ], anticonvulsants [ 20 ], and so on. Several conventional analogues of isatin are currently being used for medicinal purposes, and some representative examples of marketed drugs containing isatin scaffolds against multiple diseases/disorders are displayed in Figure 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Isatin derivatives revealed a fascinating array of pharmacological activities, such as anticancer [ 10 ], anti-HIV [ 11 ], antiviral [ 12 ], antitumor [ 13 ], antifungal [ 14 ], antimalarial [ 15 ], antioxidant [ 16 ], anti-inflammatory [ 17 ], antimicrobial [ 18 ], analgesic [ 19 ], anticonvulsants [ 20 ], and so on. Several conventional analogues of isatin are currently being used for medicinal purposes, and some representative examples of marketed drugs containing isatin scaffolds against multiple diseases/disorders are displayed in Figure 2 .…”
Section: Introductionmentioning
confidence: 99%
“…From 2D and 3D interaction diagrams of elvitegravir (Table 4, Figure 5), it was found that standard inhibitor binds to the target site; showed hydrogen bonding interaction with LYS 101, ILE-180, and LEU-100 and docking score (-8.57). The standard drug rilpivirine also showed hydrogen bonding with LYS 101; its docking score was -8.56 (literature value = -7.61) [33]. The designed compounds fit best in the allosteric site of HIV reverse transcriptase.…”
Section: Molecular Docking Studiesmentioning
confidence: 93%
“…In their quest to develop new anti-HIV therapeutics, Pawar et al [ 45 ] designed various isatin analogs [ 14 ] (Fig. 16 ).…”
Section: Isatin Derivatives As Anti-hiv Agentsmentioning
confidence: 99%